2022
DOI: 10.1177/15271544221112893
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Leadership Competencies Through Population Health Policy Advocacy: A Review of the Evidence

Abstract: The purpose of this article is to identify the gaps in prelicensure nursing curriculum regarding the teaching and learning of policy advocacy and the necessary nursing leadership competencies that are significant in addressing social determinants of health at an upstream, policy level and to discuss how current prelicensure nursing curricula integrates and applies concepts of population health, policy advocacy, and nursing leadership competencies. The authors performed a conceptual review of the literature, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 22 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Local healthcare planning by PHNs is an upstream strategy that is a good opportunity for both the development of needs‐oriented policies and enhancement of health equity (Cropley et al., 2022; Greer et al., 2022). Health policy development is essential competency of PHNs (APHA & Public Health Nursing Section, 2013; QCC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Local healthcare planning by PHNs is an upstream strategy that is a good opportunity for both the development of needs‐oriented policies and enhancement of health equity (Cropley et al., 2022; Greer et al., 2022). Health policy development is essential competency of PHNs (APHA & Public Health Nursing Section, 2013; QCC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about US nursing and midwifery students' instruction on health policy, their educational experiences around advocacy, or their political participatory behaviors and attitudes. 3,4,8,9 A 2022 literature review on policy advocacy curriculum in prelicensure nursing programs found inconsistent teaching strategies. A lack of evidence regarding the effectiveness of different pedagogical approaches was noted, with no consensus on essential topics in health policy curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 Curricular strategies are described as too broad and ambitious, resulting in ambiguity and ineffectiveness. 4 The importance of tailoring health policy curricula to the role of the nurse at each level of nursing education, weaving health policy content into other didactic courses, and engaging nursing faculty in health policy activities as role models was emphasized. 4,9,25 The AACN published a 2021 revised framework for nursing curriculum that incorporated recommendations to improve health policy instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations